Technical and Economic Analysis of Distillation Column Design in the Biodiesel Industry - Sanjoyo, Bandung Arry; Erwan Adi Saputro; Ahmad Rizaldi (International Journal of Natural Science and Engineering, 2024)
The distillation column is one of the vital components in the biodiesel industry equipment, functioning to separate biodiesel compounds from other compounds such as glycerin and residual methanol. This research aims to analyze future predictions of distillation column prices based on the specified equipment specifications. This type of research is quantitative research with a descriptive approach. The type of research used in this study is quantitative descriptive research with a case study approach and technical simulation. In this study, the methodology used to estimate distillation equipment costs in biodiesel production involves a comprehensive two-stage approach: Equipment specifications are determined based on production capacity, and then price estimates are carried out using the Peters & Timmerhaus formula. In this research, the sample used is technical and economic data related to distillation column design in the biodiesel industry. The calculation data is compared with actual prices on the market to validate the accuracy of the method. The data analysis technique used is economic engineering estimation calculations accompanied by empirical comparisons. The research results show that increasing production capacity requires larger distillation column specifications, such as tower diameter, tower height, and number of holes in the tray, and more complex supporting accessories to support optimal performance. Price comparison shows that the estimation method using the Peters & Timmerhaus formula produces fairly accurate predictions of current market prices. These findings imply that this method can be used as an adequate approach to planning the procurement of distillation columns in the biodiesel industry more efficiently. The implications of this research show that optimal distillation column design not only increases the efficiency of the biodiesel purification process but also significantly reduces operational costs and initial investment. From a technical perspective, proper design can increase product purity, reduce energy consumption, and extend equipment life, ultimately improving overall plant performance.